Effect of dexmedetomidine on liver transplantation: a meta-analysis - Degong Jia; Shanshan Guo; Xinyi Wu; Minjie Zhao; Jiefu Luo; Mingxiang Cheng; Yajun Qin (Frontiers Media S.A., 2023)
Background: Dexmedetomidine (DEX), an adjuvant anesthetic, may improve the clinical outcomes of liver transplantation (LT).Methods: We summarized the relevant clinical trials of DEX in patients undergoing LT. As of 30 January 2023, we searched The Cochrane Library, MEDLINE, EMBASE, Clinical Trial.gov and the WHO ICTRP. The main outcomes were postoperative liver and renal function. The random effect model or fixed effect model was used to summarize the outcomes across centers based on the differences in heterogeneity.Results: The meta-analysis included nine studies in total. Compared with the control group, the DEX group had a reduced warm ischemia time (MD-4.39; 95% CI-6.74−‐2.05), improved postoperative liver (peak aspartate transferase: MD-75.77, 95% CI-112.81−‐38.73; peak alanine transferase: MD-133.51, 95% CI-235.57−‐31.45) and renal function (peak creatinine: MD-8.35, 95% CI-14.89−‐1.80), and a reduced risk of moderate-to-extreme liver ischemia-reperfusion injury (OR 0.28, 95% CI 0.14-0.60). Finally, the hospital stay of these patients was decreased (MD-2.28, 95% CI-4.00−‐0.56). Subgroup analysis of prospective studies showed that DEX may have better efficacy in living donors and adult recipients.Conclusion: DEX can improve short-term clinical outcomes and shorten the hospital stay of patients. However, the long-term efficacy of DEX and its interfering factors deserves further study.Systematic Review: identifier CRD42022351664.